1998
DOI: 10.1111/j.2044-8260.1998.tb01397.x
|View full text |Cite
|
Sign up to set email alerts
|

The mental health of Muslim mothers in extended families living in Britain: The impact of intergenerational disagreement on anxiety and depression

Abstract: The unusually high levels of depression and anxiety displayed by Muslim mothers living in extended families can in part be accounted for by patterns of intergenerational discrepancy. These possibly reflect discordant world views within those families that have been assimilated into the dominant British culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…However, this dichotomy in terms of cultural orientation may leave individuals in a vulnerable state. Some research specific to Muslims suggests that individuals who do not share the same traditional cultural beliefs and values of their extended family may be at risk for mental health problems (Sonuga‐Barke & Mistry, 2000; Sonuga‐Barke et al, 1998). Hence, we hypothesized that a match between personal and family acculturation would be associated with less depression; by the same token, a mismatch should be associated with more depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this dichotomy in terms of cultural orientation may leave individuals in a vulnerable state. Some research specific to Muslims suggests that individuals who do not share the same traditional cultural beliefs and values of their extended family may be at risk for mental health problems (Sonuga‐Barke & Mistry, 2000; Sonuga‐Barke et al, 1998). Hence, we hypothesized that a match between personal and family acculturation would be associated with less depression; by the same token, a mismatch should be associated with more depression.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no studies that directly explore the relationship between the degree of personal–family acculturation match and depression in Muslims, there is indirect evidence for this association. In a study that explored the consequences of intergenerational differences regarding childrearing on the mental health of Muslim mothers living in extended families, Sonuga‐Barke, Mistry, and Qureshi (1998) found high rates of depression and anxiety in Muslim mothers. Muslim mothers espoused less traditional childrearing beliefs than did Muslim grandmothers, and this discrepancy was stronger in more acculturated nuclear families (i.e., excluding grandparents).…”
mentioning
confidence: 99%
“…Research has demonstrated that traditionalism in family structures may have a detrimental effect for some South Asian women and for particular generations (Sonuga-Barke et al, 1998). These studies have shown positive effects of extended family living for Muslim children and their grandmothers but negative effects for Muslim mothers.…”
Section: Mental Health and Acculturationmentioning
confidence: 98%
“…Cultural and linguistic differences may hinder the detection and treatment of PND among South Asian communities 10 . Muslim mothers living in extended families have been reported to display unusually high levels of depression and anxiety 11 . UK women of South Asian descent who were born in India or East Africa have a 40% higher suicide rate than women born in England and Wales…”
mentioning
confidence: 99%